2015
DOI: 10.1111/cid.12363
|View full text |Cite
|
Sign up to set email alerts
|

Platform‐Switching for Cemented Versus Screwed Fixed Dental Prostheses: Reliability and Failure Modes: An In Vitro Study

Abstract: The probability of survival of cement-retained ISFDP was higher than screw-retained, irrespective of implant-abutment horizontal configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
4
13
0
Order By: Relevance
“…For all groups, failure predominantly involved abutment screw fracture. Two representative fractographic analyses are presented in Figs and for external hexagon implant groups, whereas for internal hexagon implant groups the same patterns have been reported elsewhere . The abutments remained intact in ERC and ESC groups after mechanical testing.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…For all groups, failure predominantly involved abutment screw fracture. Two representative fractographic analyses are presented in Figs and for external hexagon implant groups, whereas for internal hexagon implant groups the same patterns have been reported elsewhere . The abutments remained intact in ERC and ESC groups after mechanical testing.…”
Section: Resultssupporting
confidence: 57%
“…The performance of ISFDPs (where abutment splinting may have a more prominent effect than the abutment material) or fixation method has been less explored. A recent fatigue study performed by our group showed that the fixation method had a significant impact on the survival of ISFDPs, with a lower percentage of survival for screwed restorations compared with cemented restorations , which is in agreement with a systematic review . On the other hand, it is unknown whether the performance of cemented three‐unit FDPs with mismatched platform is influenced by the implant–abutment connection design.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…On the other hand, the literature demonstrates that cemented prostheses have been associated with a higher risk for peri-implantitis probably due to the occurrence of residual cement in the peri-implant sulcus (26). The greater possibility of misfit or fractures of the screwed prostheses may have increased the gap size and contributed to the presence of peri-implantitis (27). However, the information about the prosthetic complications was not provided by this study.…”
Section: Discussionmentioning
confidence: 70%